Overcoming the Neonatal Limitations of Inducing Germinal Centers through Liposome-Based Adjuvants Including C-Type Lectin Agonists Trehalose Dibehenate or Curdlan - Vono, Maria; Eberhardt, Christiane Sigrid; Mohr, Elodie; Auderset, Floriane; Christensen, Dennis; Schmolke, Mirco; Coler, Rhea; Meinke, Andreas; Andersen, Peter; Lambert, Paul-Henri; Mastelic-Gavillet, Beatris; Siegrist, Claire-Anne (Frontiers in Immunology, 2018)
Neonates and infants are more vulnerable to infections and show reduced responses to vaccination. Consequently, repeated immunizations are required to induce protection and early life vaccines against major pathogens such as influenza are yet unavailable. Formulating antigens with potent adjuvants, including immunostimulators and delivery systems, is a demonstrated approach to enhance vaccine efficacy. Yet, adjuvants effective in adults may not meet the specific requirements for activating the early life immune system. Here, we assessed the neonatal adjuvanticity of three novel adjuvants including TLR4 (glucopyranosyl lipid adjuvant-squalene emulsion), TLR9 (IC31®), and Mincle (CAF01) agonists, which all induce germinal centers (GCs) and potent antibody responses to influenza hemagglutinin (HA) in adult mice. In neonates, a single dose of HA formulated into each adjuvant induced T follicular helper (TFH) cells. However, only HA/CAF01 elicited significantly higher and sustained antibody responses, engaging neonatal B cells to differentiate into GCs already after a single dose. Although antibody titers remained lower than in adults, HA-specific responses induced by a single neonatal dose of HA/CAF01 were sufficient to confer protection against influenza viral challenge. Postulating that the neonatal adjuvanticity of CAF01 may result from the functionality of the C-type lectin receptor (CLR) Mincle in early life we asked whether other C-type lectin agonists would show a similar neonatal adjuvanticity. Replacing the Mincle agonist trehalose 6,6′-dibehenate by Curdlan, which binds to Dectin-1, enhanced antibody responses through the induction of similar levels of TFH, GCs and bone marrow high-affinity plasma cells. Thus, specific requirements of early life B cells may already be met after a single vaccine dose using CLR-activating agonists, identified here as promising B cell immunostimulators for early life vaccines when included into cationic liposomes.